Eyes on the alley: children's appropriation of alley space in Riverdale, Toronto. Issue 2 (4th March 2019) - Furneaux, Alexander; Manaugh, Kevin
ABSTRACT: Recent research suggests that numerous positive physical, cognitive, and social benefits can be derived from independent mobility and play agency amongst children, necessitating an understanding of how physical and social environments facilitate this development. This study involved parents, and children aged 9–13 from twelve households in the neighbourhood of Riverdale in Toronto. Using a mapping exercise to instigate discussion, participants were asked to describe where, how, and with whom play occurs in their neighbourhood. A reoccurring theme emerged amongst households that border a back alley where parents perceived this space as safer allowing them to grant greater independent mobility to their children and use this space as an intermediary tool to prepare their children for greater independence. For children, this space serves as one of creative appropriation, granting them access to more space and friends to play with. Situated within the context of age-friendly cities, this research identifies several socio-spatial qualities found in alleys that have the potential to contribute to the discussion of more inclusive city-building practice.